Discussing Borders, Escaping Traps - Franck Orban (Waxmann Verlag, 2019)
We live in strange times. Old borders are vanishing just before our astonished eyes, while new ones are rapidly emerging. Nearly three decades after the publication of Francis Fukuyama's The End of History and the Last Man, the zeitgeist that predicted a bright future for mankind to a large extent turned out to be rather more of a dystopia. Crises in and outside Europe multiplied the number of border controls, triggered the construction of walls and fences and widened ideological gaps. The book Discussing Borders, Escaping Traps is a transdisciplinary and transspatial approach to investigating these vanishing, emerging and changing material and immaterial borders. It is the result of a two-year project by AreaS, a research group in area studies located at Østfold University College in Norway, and by partners of AreaS.